Development of profit-loss cost utility function for task allocation/scheduling in cloud data centers - Phan, Minh Nhat (2018)
In recent years we have experienced a significant increase in total energy consumption of data centers due to the fast growth of internet usage and cloud-based solutions. The energy consumption cost thus becomes one of the most significant challenges for cloud service providers and data center builder. An intelligent energy cost-aware task allocation and scheduling strategy can be a potent tool in addressing this issue. Due to a high cost of testing and experimenting in real data centers, many algorithms have been developed using simulation frameworks to provide a good strategy for reduction of energy consumption. Nevertheless, there is a lack of algorithms focus on temperature balancing, even though the harmful effects of high temperature and the costs of cooling systems are drastically high. The purpose of this project is to develop a thermal-aware profit-loss cost-utility function which can assist in predicting the profit or loss when allocating an application to a data center.